Gastrodin: a potential natural product for the prevention and treatment of cerebral ischemia-reperfusion injury - Qin, Wenxiu; Du, Jianqiang; Wang, Feng; Xu, Junfeng (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceGastrodin is the main bioactive metabolite of Gastrodia elata Blume of traditional Chinese medicine, which has pharmacological effects such as anti-inflammatory, antioxidant, neuroprotective, vasoprotective, hypoglycemic, lipotropic, analgesic, anticancer, antiviral and so on, and it has been widely used in the treatment of a wide range of diseases, especially neurological disorders.Aim of the reviewCerebral ischemia-reperfusion injury (CIRI) is defined as transient or permanent ischemia of brain tissue that is further exacerbated by restoration of blood supply. Due to the complexity of the pathological processes of CIRI, current treatments have not shown the expected effects. More and more researchers are beginning to turn their focus on combating CIRI to natural metabolites derived from botanical drugs. This review provides an overview of the progress of research on the chemical composition, pharmacokinetics, safety, and pharmacological effects of Gastrodin in the treatment of CIRI. It aims to emphasize the important pharmacological effects and mechanisms of Gastrodin in the prevention and treatment of CIRI, and to provide reference for further drug research and development, as well as the future application of Gastrodin in CIRI.Materials and methodsA systematic literature search was conducted using keywords such as “Gastrodin,” “traditional Chinese medicine,” “chemical components,” “metabolites,” “cerebral ischemia-reperfusion injury,” “CIRI,” and “pharmacological effects” to identify relevant literature published from the establishment of the database to January 2025. Databases including PubMed, Web of Science, Google Scholar, and CNKI were utilized. Raw data were included in clinical trials and animal experiments. Other studies, such as reviews and systematic evaluations, were excluded.ResultsGAS can prevent and treat cerebral ischemia/reperfusion-induced neurological injury by regulating a variety of molecular signals, exerting pharmacological effects such as anti-oxidative stress, inhibition of inflammatory response, inhibition of cell death, modulation of neurotransmitters, alleviation of neurotoxicity, promotion of neural repair, protection of the blood-brain barrier, and alleviation of cerebral edema, making it a potential natural metabolite for the effective treatment of CIRI.ConclusionGastrodin has significant value in the treatment of CIRI and there is extensive evidence to support its use in CIRI. Further research and clinical exploration of Gastrodin is necessary to fully utilize its therapeutic potential.